Using eye-tracking to investigate teacher gaze: Data accuracy and drawing of meaningful dynamic areas of interest in video stimuli - Christina Ioanna Pappa; Christian Kosel; Katharina Schnitzler; Tina Seidel (Czech Pedagogical Society, 2020)
Studies that investigate teacher attention via eye-tracking methodology display variety in their reporting styles and consideration of their data quality. This may be due to the fact that eye-tracking has been newly introduced in teacher research, and systematic guidelines are not yet established. This especially accounts for the influence of the quality of the raw data (i.e., accuracy level) and the way that the raw data is processed through the drawing of dynamic areas of interest (AOIs) in video stimuli. The present study investigates the influence of various accepted accuracy levels on the number of fixations and three variations of AOI drawings (student shape, indicated by outlined areas; face, indicated by ovals; and student area, indicated by rectangles) on common eye-tracking metrics: number of fixations, glances, and fixation duration. Sixty-two participants observed a video stimulus with five marked students as the targeted AOIs. A one-way ANOVA was conducted to examine the influence of different accuracy levels (>1°, > 0.5° to ≤ 1.0°, and ≤ 0.5°) of the data on the number of fixations, while the effect of three different dynamic AOI shapes (student shape, face, rectangle) was investigated with a series of repeated-measure one-way ANOVAs. The results indicated no significant difference between the accuracy levels and the number of fixations. For the different AOI shapes, significant differences were observed. When using rectangles, more fixations and glances were recorded in contrast to the other two forms. The average fixation duration was greatest when only the faces were marked. This indicates that depending on the research question and the position of the AOIs, researchers may choose different forms of AOIs and consider the accuracy of their data.